INFERIOR EPIGASTRIC ARTERY USE IN KIDNEY TRANSPLANTS FOR UPPER POLAR ARTERY VASCULARIZATION: A CASE REPORT - Hassan, Muneeb; Iqbal, Qaiser; Mirza, Irfan; Rashid, Tahir; Khan, Taqi (Journal of Postgraduate Medical Institute, 2024)
Minimizing number of anastomoses by arterial reconstruction is critical in grafts with multiple arteries to reduce implantation warm ischemia (RWI), delayed graft function (DGF) and its complications. We report a case of successful transplantation of a donor kidney with three arteries, 2 hilar, and the third entering the upper pole. The kidney was implanted with the ureter up allowing the upper polar artery (UPA) to be vascularized by the inferior epigastric artery (IEA) after de-clamping, avoiding extra RWI. A 29-year-old male with bilateral multiple renal arteries donated to a 37-year-old male recipient. The right kidney had 2 arteries with 3 arteries on the left, but since the right renal vein was deemed short, it was decided to use the left kidney. A single lumen was created for the two larger hilar arteries and the UPA appeared appropriate for end-to-end anastomosis to IEA. The kidney was implanted upside down, with the ureter up, placing the upper pole laterally in proximity to the dissected IEA. The kidney was perfused after completing the single lumen anastomosis to the external iliac artery (EIA). The UPA was then anastomosed to the IEA with immediate graft function. This can be a viable option in grafts with multiple arteries including a UPA, to ensure global perfusion without prolonging RWI and avoiding DGF.